A note on invariant submanifolds of $(k, μ)$-contact manifolds - Avik, De (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The object of the present paper is to study invariant submanifolds of a $(k, μ)$-contact manifold and to find the necessary and sufficient conditions for an invariant submanifold of a $(k, μ)$-contact manifold to be totally geodesic.